ChemInform Abstract: Ionic Liquid Promoted Diazenylation of N‐Heterocyclic Compounds with Aryltriazenes under Mild Conditions. Issue 38 (September 2016) - Cao, Dawei; Zhang, Yonghong; Liu, Chenjiang; Wang, Bin; Sun, Yadong; Abdukadera, Ablimit; Hu, Haiyan; Liu, Qiang
Abstract: The mild, metal‐free reaction provides various N‐heterocyclic azo substituted indole derivatives in very high yields.